Social Influence in Adolescent Decision-Making: A Formal Framework - Ciranka, Simon; van den Bos, Wouter (Frontiers in Psychology, 2019)
Adolescence is a period of life during which peers play a pivotal role in decision-making. The narrative of social influence during adolescence often revolves around risky and maladaptive decisions, like driving under influence and using illegal substances (Steinberg, 2005). However, research has also shown that social influence can lead to increased prosocial behaviours (Van Hoorn, Crone, & Van Leijenhorst, 2017) and a reduction in risk-taking (Braams, Davidow, & Somerville, 2019). While many studies support the notion that adolescents are more sensitive to peer influence than children or adults, the developmental processes that underlie this sensitivity remain poorly understood. We argue that one important reason for this lack of understanding is the absence of precisely formulated models. To make a first step towards formal models of social influence during adolescence, we first identify three prominent verbal models of social influence in the literature: (1) social motivation, (2), reward sensitivity and (3) distraction. We then illustrate how these can be translated into formal models, and how such formal models can inform experimental design and help identify developmental processes. Finally, by applying our formal models to existing datasets, we demonstrate the usefulness of formalization by synthesizing different studies with seemingly disparate results. We conclude with a discussion on how formal modelling can be utilized to better investigate the development of peer influence in adolescence.